Reversed Active Sites Boost the Intrinsic Activity of Graphene‐like Cobalt Selenide for Hydrogen Evolution. (26th April 2021) - Shen, Shijie; Lin, Zhiping; Song, Kai; Wang, Zongpeng; Huang, Liangai; Yan, Linghui; Meng, Fanqi; Zhang, Qinghua; Gu, Lin; Zhong, Wenwu
Abstract: Optimizing the hydrogen adsorption Gibbs free energy (Δ G H ) of active sites is essential to improve the overpotential of the electrocatalytic hydrogen evolution reaction (HER). We doped graphene‐like Co0.85 Se with sulfur and found that the active sites are reversed (from cationic Co sites to anionic S sites), which contributed to an enhancement in electrocatalytic HER performance. The optimal S‐doped Co0.85 Se composite has an overpotential of 108 mV (at 10 mA cm −2 ) and a Tafel slope of 59 mV dec −1, which exceeds other reported Co0.85 Se‐based electrocatalysts. The doped S sites have much higher activity than the Co sites, with a hydrogen adsorption Gibbs free energy (Δ G H ) close to zero (0.067 eV), which reduces the reaction barrier for hydrogen production. This work provides inspiration for optimizing the intrinsic HER activity of other related transition metal chalcogenides. Abstract : Graphene‐like Co0.85 Se was doped with sulfur, bringing about a reversal in active sites for the electrocatalytic hydrogen evolution reaction (HER) from cationic cobalt sites to anionic sulfur sites. A consequent change in the hydrogen adsorption Gibbs free energy (ΔGH) of the active sites improved the overpotential of the HER.